2008
DOI: 10.1590/s0102-311x2008000400025
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e percepção da doença entre portadores de hipertensão arterial

Abstract: IntroduçãoA hipertensão arterial é considerada um dos fatores de risco mais importantes para o desenvolvimento de doenças cardiovasculares e sofre influência multifatorial, com destaque para o estilo de vida 1 .Conforme se indica, concomitante à terapêu-tica para o controle da hipertensão arterial, os indivíduos devem adotar um estilo de vida saudável, eliminando hábitos que constituam fatores de risco para a doença. Entretanto, no acompanhamento à saúde dos pacientes, segundo se observa, é grande a dificuldad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
47

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 4 publications
3
16
0
47
Order By: Relevance
“…Among others, this domain had the highest score, with a mean value of 77.8 (SD 26.1), which is consistent with other studies in which this domain also had the highest score, with values ranging from 69.3 to 77.0 5,21,25 . The influence of HA in this aspect may be due to the need to change your lifestyle, including eating habits, which often involves absence from family gatherings to avoid inadequate food intake.…”
Section: Vitality (Vit)supporting
confidence: 89%
See 2 more Smart Citations
“…Among others, this domain had the highest score, with a mean value of 77.8 (SD 26.1), which is consistent with other studies in which this domain also had the highest score, with values ranging from 69.3 to 77.0 5,21,25 . The influence of HA in this aspect may be due to the need to change your lifestyle, including eating habits, which often involves absence from family gatherings to avoid inadequate food intake.…”
Section: Vitality (Vit)supporting
confidence: 89%
“…The study that received the lowest score was the one by Souza 14 , averaging 45.1. In the study by Brito et al 25 we obtained the mean value of 63.3. The authors also suggest that living with hypertension interferes with physical condition, subject to the comments related to fatigue related to age, disease duration and others.…”
Section: Vitality (Vit)mentioning
confidence: 76%
See 1 more Smart Citation
“…Another investigation using the same generic instrument demonstrated that the QOL of 131 hypertensive subjects presented physical and emotional compromising 27 . Our results demonstrated that initially the worse scores were emotional, exactly the ones which presented the best significant improvement in the EG.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials and behavioral changes of individuals in the face of specific treatments provided the establishment of measures in the accurate assessment of the answers of the health profile of the patients [10]. Several instruments and scales have been developed to assess the quality of life and one of them is the SF-36 (Medical Outcomes Study 36-Item Short-Form Health Survey).…”
mentioning
confidence: 99%